Sketching the Global Social Media Landscape = Küresel sosyal medya alanının Avrupa ve Hollanda'ya odaklanarak Taslaklandırılması - Reijgersberg, Maarten (Eastern Mediterranean University, Social Media Unit, 2016)
Maarten Reijgersberg is the founder of and social media architect at RauwCC, social media the Rotterdam way. RauwCC is ranked as the number one social agency in The Netherlands by Emerce 100/2015. Maarten is also the founder of Social Media Week Rotterdam, the largest annual conference on social media and innovation in the Benelux region. Besides his work at RauwCC and Social Media Week Rotterdam, Maarten is the founder of Social Media Signage, the window to your online activity. Social Media Signage is a high tech narrowcasting solution for companies to broadcast their social media activities to an offline audience. In the year 2000 Maarten graduated from the Willem de Kooning Academy in Rotterdam with a bachelor degree in autonomous arts. After which he gained a lot of experience as a graphic designer and art director at various agencies. He worked with a wide range of corporate and governmental clients. Maarten has a huge network, online as well as offline. He's radical, straightforward, practical and always on the verge of technology.
Eastern Mediterranean University, Social Media Unit, in collaboration with EMU Communication and Media Studies Faculty, is organising a “Social Media and Brand Week” between 6 and 7 April 2016.
Keywords: Social Media